Richness and abundance of non-flying terrestrial mammals in an urban environment in the Neotropic - Salas-Solano, Diego (2025)
Introduction: Urban green spaces are becoming increasingly important refuges for native fauna. In Costa Rica, most of the human population is concentrated in the Central Valley, producing drastic changes in natural ecosystems as urbanization increases and consequently reducing the natural habitats of multiple species. Urban development generally decreases the native diversity of mammals. Objective: We described the richness and abundance of medium-sized terrestrial mammals in fragments of second growth and secondary forest vegetation immersed in an urban matrix. Methods: We conducted a landscape analysis to measure the green spaces and urban land cover, and surveyed terrestrial mammals using night baiting traps, diurnal counts in transects, camera traps, and occasional reports. Results: We found six native and three introduced species of terrestrial mammals, representing less than 50% of the medium-sized mammal diversity reported for the Central Valley of Costa Rica 40 years ago. The common raccoon (Procyon lotor) and the variegated squirrel (Sciurus variegatoides) were the most abundant species, both capable of exploiting urban habitats. Introduced species, especially free-ranging and feral cats (Felis catus), were the most common species in the study site. Free-ranging introduced species may increase predation and disease transmission. Fragmentation, isolation, and lack of connectivity caused by urbanization are likely affect the populations of sloth species (Bradypus variegatus and Choloepus hoffmanni) in the study site.  Conclusion: Maintaining natural and seminatural spaces and native vegetation is essential to conserve urban biodiversity.